2015
DOI: 10.1038/nm.3774
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase 3a regulates osteoclast differentiation by coupling to an S-adenosylmethionine–producing metabolic pathway

Abstract: Metabolic reprogramming occurs in response to the cellular environment to mediate differentiation, but the fundamental mechanisms linking metabolic processes to differentiation programs remain to be elucidated. During osteoclast differentiation, a shift toward more oxidative metabolic processes occurs. In this study we identified the de novo DNA methyltransferase 3a (Dnmt3a) as a transcription factor that couples these metabolic changes to osteoclast differentiation. We also found that receptor activator of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
176
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 44 publications
9
176
0
1
Order By: Relevance
“…Moreover, the basal OCR was greatly increased by the ectopic expression of MYC ( Figure 3G). Consistent with previous reports (7,16), perturbation of metabolic pathways such as glutaminolysis, glycolysis, and oxidative phosphorylation using specific inhibitors severely abrogated osteoclast differentiation (Supplemental Figure 10), implicating the significance of metabolic reprogramming in osteoclastogenesis. Collectively, these results indicate that MYC is a crucial regulator of RANKL-activated mitochondrial respiration that supports an increased energy demand during osteoclast differentiation.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Moreover, the basal OCR was greatly increased by the ectopic expression of MYC ( Figure 3G). Consistent with previous reports (7,16), perturbation of metabolic pathways such as glutaminolysis, glycolysis, and oxidative phosphorylation using specific inhibitors severely abrogated osteoclast differentiation (Supplemental Figure 10), implicating the significance of metabolic reprogramming in osteoclastogenesis. Collectively, these results indicate that MYC is a crucial regulator of RANKL-activated mitochondrial respiration that supports an increased energy demand during osteoclast differentiation.…”
Section: Resultssupporting
confidence: 90%
“…Taken together, these results suggest that ing the essential role of MYC in meeting energy and anabolic demands during osteoclast differentiation. In previous studies, increased oxidative phosphorylation has been partially mediated by increased mitochondrial biogenesis orchestrated by PGC1β (18) and is accompanied by an increase in S-adenosylmethionine (SAM) production (16). We have observed that the effect of MYC on oxidative phosphorylation is independent of mitochondrial biogenesis and that the overexpression of MYC is unable to regulate PGC1β expression, which suggests the uncoupling of PGC1β from oxidative phosphorylation in osteoclastogenesis.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations